Risk assessment, diagnosis, and treatment of cancer treatment-related adrenal insufficiency. Issue 1 (2nd January 2022) - Hayes, Annabelle G; Rushworth, R. Louise; Torpy, David J
ABSTRACT: Introduction: Adrenal insufficiency (AI) is an easily treatable, potentially life-threatening condition, which is increasingly recognized in malignancy. The recent introduction of immune checkpoint inhibitors, in particular, and increasing use of tyrosine kinase inhibitors have increased the frequency of AI in patients with malignancy. A review is therefore warranted to summarize current knowledge on the topic and guide safe clinical practices. Areas Covered: Malignancy may directly impact the hypothalamic-pituitary-adrenal axis and cause AI, or their treatment including surgery, radiotherapy and medication. In this narrative review, we discuss new causes of AI, recognition of suggestive clinical features, diagnosis and subsequent treatment, aiming to avoid potentially fatal adrenal crisis (AC). Standard literature searching and authors assessment of clinical applicability were used. Expert Opinion: Adrenal insufficiency can be easily treated once identified but life threatening if unrecognized. While use of new agents such as immune checkpoint inhibitors (ICIs) is increasing, greater understanding of the mechanism of AI is needed to target prediction tools and enhance risk stratification.